Procrastination of islamic religious education students reviewed from the level of learning motivation and achievement motivation - Istinganah, Istinganah; Kistoro, Hanif Cahyo Adi (Al-Misbah (Jurnal Islamic Studies), 2024)
Learning plays a crucial role in achieving educational goals by providing new knowledge to individuals. In learning, a person needs motivation, including learning motivation and achievement motivation. Someone who is less motivated tends to procrastinate in completing his tasks. This procrastinating behavior can lead to negligence and hinder a person's ability to complete all tasks. The purpose of this study was to determine whether learning motivation and achievement motivation influence the procrastination of Islamic Education students of Ahmad Dahlan University.This study used a quantitative approach. In this study, a simple random sampling technique was used with a sample of 128 students of Islamic Education at Ahmad Dahlan University. The independent variables in this study were learning motivation (X1) and achievement motivation (X2), while the dependent variable was procrastination (Y). Researchers used data collection techniques in the form of questionnaires. The data analysis method in this study involves applying simple linear regression analysis and multiple linear regression analysis using SPSS 25 for Windows software. This study showed that there was no influence between learning motivation and the procrastination of PAI UAD students because the t count did not show the opposite influence. Second, there is an influence between achievement motivation and the procrastination of PAI UAD students by 69.1%, with a confidence level of 95%. Third, there is no simultaneous influence between learning motivation and achievement motivation on the procrastination of PAI UAD students because the significance value on the learning motivation variable is more than 0.05, and the t count does not show the opposite influence. Thus, H2 a was accepted in this study, while H1 a and H3 a were rejected.